The Face Mask Waste Recycling Generated During Covid-19 Pandemic In Indonesia - Hamdani, Ahmad Helman; Haryanto, Agus Didit (Faculty of Geological Engineering, Universitas Padjadjaran, 2021)
In Indonesia, the COVID-19 disease has developed rapidly as found on April 20, 2021, there were 1,614,849 positive cases of Covid-19. The increase in cases of the coronavirus has resulted in an increase in the amount of medical waste during the Covid-19. The most common medical waste is face masks, both from hospitals and households. This increase in medical waste will cause environmental damage or health problems.